A gestão dos riscos no cenário da aids: um estudo sobre as estratégias adotadas por homens que fazem sexo com homens em parceria casual - Luiz, George Moraes de (2011)
This study is focused on risk management strategies in the Aids scenario. Risk management involves five integrated strategies: the safe ones, the laws of damage responsibility, direct government intervention, self-regulation and the communication of the risks. The notion of risk has been gradually changed into a less technical approach and as it was influenced by the sociological perspective developed by Ulrich Beck (1993) and Anthony Giddens (1991), it started to acquire critical character. In this context, risk is considered in its relation with the socio-political conditions of the late modernity societies. In the last two decades, anthropologist Mary Douglas (1982, 1985, 1987, 2000) has added cultural aspects to the discussion of risk evaluation, questioning the hegemony of the objectivists trends. To understand risk management, it is now taken into examination the practices of sex between two men in casual encounters or partnerships. The theories and methodologies on which this study is based are the concepts of sexual practices (PARKER, 1994, 1995, 1997, 2002,) and risky life styles (CASTIEL, 1996, 2006; SPINK, 2001, 2002, 2003, 2007). Through the technique known as snow ball, ten subjects were selected to be interviewed within the field of discursive practices from the perspective of quotidian conversations (SPINK, 2000). The information gathered leads us into thinking about the relation between social and cultural factors and the production of risky life styles. Another question is the assimilation of science-based data that is found within the quotidian social context and are interpreted as a potential source for risk management. It is also highlighted the usage of information that is not technically-based and is related to people s beliefs and values, or that exists in the quotidian social context and ends up being a part of the risk management repertoire. To summarize, it seems possible to state that when men who have sex with men choose to do so without using a prophylactic, they develop their own strategies with the intention of decreasing the possibility of STD/HIV infection and/or second infection by HIV, without basing themselves on official government prevention policies. The conclusion is that such pieces of information work as safety belts that allow them to take risks in a safe zone even in a scenario of incertitude